Tingkat Kecemasan Pasien Kanker Payudara Yang Menjalani Kemoterapi Dimasa Pendedemi Covid-19 - Fadillah Fadillah; Sanghati Sanghati (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: Breast cancer is a moderately severe disease characterized by uncontrolled growth and the continuous spread of abnormal cells that can damage the surrounding tissues. Goal: Anxiety levels of breast cancer patients undergoing chemotherapy during the Covid-19 pandemic. Method: Qualitative research with a case study approach. Kuesinoer Hamilton Rating Scale for Anxiety (HRS-A) measuring slat. Result: Showed the subject that I had undergone chemotherapy with a score of 25 in the moderate anxiety category. In subject II, the score was: 39 in the severe anxiety category. In subject III, the score resulted: 42 with a category of severe anxiety once. Conclusion: The anxiety level of breast cancer patients while undergoing chemotherapy varies with experienced and inexperienced chemo cycles during the Covid-19 period. Hospitals are expected to continue improving professional services, especially for breast cancer patients undergoing chemotherapy, which can assess the anxiety of breast cancer patients undergoing chemotherapy.